Consumption based capital asset pricing and the Austrian Stock Exchange - René Böheim; Michael Boss (Institute for Advanced Studies (IHS), 1996)
Using data from the Vienna Stock Exchange we investigate three different types of consumption based capital asset pricing models: the well known two state model of Mehra and Prescott, the model of Rietz, which includes also a crash state, and an own four state model. The aim of this Vienna Stock Exchange during the 1980s into account. For all the models we calculate the risk premium in order to see whether the models could explain the empirically observed risk premium. For the calculation of risk premia we use estimators generated by the General Method of Moments.
Keywords: G12; 330; consumption based capital pricing models; GMM; equity premium puzzle; Risikoprämie; Portfolio-Management; Capital Asset Pricing Model; Konsumtheorie; Schätztheorie; Theorie